Salivary Cortisol Level Pre and Post MRI Scanning - Maha Jamal Abbas; Kahtan Adnan Abood; Lehad M. Al Azzawi (College of Pharmacy / Mustansiriyah University, 2016)
The measurement of salivary cortisol level has become a reliable method for studying the adrenal cortical function and it is response to different intrinsic and extrinsic factors such as medications and stressful factors.             The aims of this study is to investigate if there is difference between sex and the effect of time of testing on salivary cortisol level, pre and post was scanning, data for cortisol, Salivary Flow Rate (SFR) and PH of saliva were analyzed.             Non-stimulated salivary samples from 24 subjects (8 males, 16 females) pre and post scanning with Magnetic resonance imaging (MRI) was collected and the diurnal variation was taken into consideration for that all the pre and post scanning samples collected at the morning. Salivary cortisol was measured by ELISA technique, PH of saliva was measured by PH meter and salivary flow rate by specific equation.             The results shows there was significant difference in the level of salivary cortisol, SFR and PH of saliva pre and post examination and there was positive correlation with regard to cortisol level and PH of saliva pre and post scanning, just the salivary flow rate showed negative correlation, in addition the results revealed significant difference with regards to the sex of the participant as well as positive correlation between salivary PH and SFR in pretest phase and positive correlation between salivary cortisol level, SFR in post scanning phase.             From the results of this study we can conclude that the exposure to MRI scanning have an effect on Hypothalamic pituitary -adrenal axes and predispose to significant changes in cortisol level post scanning and this difference must be taken into consideration in concern to effect of raising the level of cortisone on other variables.